Reformatorernes kreds i Sankt Petri Kirke: Et konfessionelt maleris ikonografiske flertydighed - Bach-Nielsen, Carsten (Kirkehistoriske Samlinger, 2010)
Summary The congregation of the German Church of St. Peter’s in Copenhagen possesses a painting of the European reformers gathered at a table with a candle on it. Four representatives of the Catholic Church attempt to blow out the evangelical light. It is a well-known theme; numerous paintings have been copied form the print of Jan Houwens of Amsterdam. The Danish historian Louis Bobé however mentions another Dutch engraver, Martinus Beusecom, who apparently has been copying the original London painting. In the Danish Lutheran context and according to its inscription the painting does not depict a fictitious gathering of reformers of many confessions, but »Martin Luther with his few forerunners and many followers«. The Copenhagen painter has turned the original Calvinist theme into a Lutheran one. A replica at the Castle of Ledreborg was removed from the chapel by Count Holstein as he converted to Roman Catholicism in 1867. In 1899 he closed the Lutheran Chapel and re-opened it 1910 as a Catholic one. Local people were convinced that the count must have thrown Luther into the flames, but – according to common Lutheran belief of the 17th Century – Luther is incombustible. The painting probably survives somewhere in the attics of Ledreborg.